2019
DOI: 10.15171/ijhpm.2019.36
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Promises of Health Technologies: The Role of Early Health Economic Modeling

Abstract: Background: To assess whether early health economic modeling helps to distinguish those healthcare innovations that are potentially cost-effective from those that are not potentially cost-effective. We will also study what information is retrieved from the health economic models to inform further development, research and implementation decisions. Methods: We performed secondary analyses on an existing database of 32 health economic modeling assessments of 30 innovations, performed by our group. First, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 24 publications
(26 reference statements)
1
95
0
Order By: Relevance
“…1 Such "… broader criteria were not quantified" in their early health economic modelling, but they noted that these effects "… may limit the commercial viability of an innovation. " 1 The health services into which complex interventions are implemented are themselves, complex-adaptive systems. Such systems are characterised by interacting stakeholders, who actively pre-empt, adapt and influence the technical and social developments associated with an intervention.…”
Section: Complex Interventions and Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Such "… broader criteria were not quantified" in their early health economic modelling, but they noted that these effects "… may limit the commercial viability of an innovation. " 1 The health services into which complex interventions are implemented are themselves, complex-adaptive systems. Such systems are characterised by interacting stakeholders, who actively pre-empt, adapt and influence the technical and social developments associated with an intervention.…”
Section: Complex Interventions and Systemsmentioning
confidence: 99%
“…5 Grutters et al reported that their early health economic modelling helped to identify and pre-empt challenges; interestingly though however, only one of the 33 assessments resulted in further research into the implementation setting (ie, usual care). 1 In the context of complex systems, there may be benefit in also modelling the effectiveness of existing technologies in situ, to better understand aspects of current care pathways with the greatest capacity for improvement, to inform the design of new delivery models.…”
Section: Participatory Modelling For Iterative Development and Implemmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] For example Hartz and colleagues argue that early health economic modelling may support technology developers by providing relevant insights on strategic R&D decision-making, pre-clinical preliminary market assessments, go/no-go decisions and identification of potentially successful projects, development of future trial design, assessment of future reimbursement and pricing scenarios and price determination. 6 The work by Grutters et al, 9 recently published in IJHPM, nicely reports on real case studies providing interesting insights on how early health economic models have been actually implemented and how they have been used to assess the potential cost-effectiveness and inform further development, implementation and positioning of innovations in clinical practice. The authors disclose and discuss data on previously developed early health economic modelling assessments on 30 innovations conducted by their team, all of which were non-drug technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Grutters and colleagues described the experience of carrying out early-stage economic models to inform product development. 1 They reviewed 32 evaluations of 30 non-drug innovations that were used to support further development, research and implementation decisions. It is unclear to what extent the findings of the study can be generalised, and perhaps it should be viewed as a pilot study that highlights the potential of early economic modelling.…”
Section: Introductionmentioning
confidence: 99%